PENERAPAN PROBLEM BASED LEARNING (PBL)SEBAGAI UPAYA UNTUK MENINGKATKANAKTIVITAS BELAJAR SISWA PADA MATA PELAJARANKEWIRAUSAHAAN KELAS XI PEMASARAN 1DI SMK NEGERI 2 KEDIRI - EFENDI, ACHMAT (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
One of the problems facing the education sector in Indonesia is the lack of learning problems. One way that can be taken to support the implementation of entrepreneurship subjects learning goals is to implement a learning model PBL (Problem Based Learning) in the teaching of these subjects, so the pattern of teaching that is applied can vary. The purpose of this study is (1) Knowing how teachers ’skills in managing learning with PBL models on the subjects of entrepreneurship (2) Knowing how students’ learning activities using problem based learning (PBL). This research is a classroom action research (CAR), which consists of 3 cycles. The results of teacher activity during the application of problem-based learning models in entrepreneurial subjects in class XI Marketing 1 SMKN 2 Kediri has increased in each cycle with value - average per cycle (1) 3 (2) 3.27 (3) 3, 65 while the value - average student activity per cycle (1) 2.64 (2) 3.1 (3) 3.67. Learning outcomes of students in the learning process using problem based learning in entrepreneurship training eye in class XI marketing 1 SMK Negeri 2 Kediri has increased in each cycle with the percentage of each cycle (1) 79.07% (2) 88.37% (3) 93 , 03%. Keywords: problem based learning, activity, mastery learning.